ASOSIASI FUNGI MIKORIZA (FMA) ARBUSKULA PADA TANAMAN PENGHASIL GAHARU (AQUILARIA MALACCENSIS) - Sarina, .; Burhanuddin, .; Suryantini, Rosa (JURNAL HUTAN LESTARI, 2016)
A. malaccensis is a  plants at high economic value with aromatic resin contents that the effect of fungi infection. The increase at A. malaccensis growthwith arbuscular  mycorhizal  fungi. The purpose  at  this study to get A. malaccensis with AFM assosiation. Purpose of this study to get information of A. malaccensis. This study condueted for 2 months with take a wood sampling and random root for two level of A. malacensis in plant sampling and trees in Sungai Kelambu village, Tebas district, West Kalimantan area. Observation of soil and root samples carried out in laboratory of the Faculty of Forestry Silviculture  Tanjungpura University. This method use spora isolation through gradual proces of wet sceening on the ground, colouring the root of genus level calculate the percentage that is infected by AMF.  The result of study  was found   6 spora types of  AMF  from a genus glomus and  average  percentage of root infection was 33% (moderate) 77% (very high) include in infected  of clasify 3 and 5 level. Keyword :Aquilariamalaccensis,Arbuscular Mycorrhizal Fungi (AMF), Association